Identification of the Tourism Risks for Z-Value Based Risk Assessment (European Journal of Formal Sciences and Engineering, 2021)
The growing importance of the tourism sector to the global economy contributes to the increase of research in tourism risks assessment. In view of this tendency, the results of research in the field of the risk analysis on tourists’ travels in various countries during the last decades have been analyzed. Commonly used in these studies statistical methods allow to reveal and identify country-specific tourism risks and threats. But it is necessary to underline that relevant statistical data on risks are available not in all cases and countries. Moreover, in most cases, the reliability of the information available is questionable. In order to improve the reliability and quality of the tourist risk assessment, it is proposed to consider tourist travel as a project. The proposed project approach to tourist risk analysis provides an opportunity to go beyond assessment based on available country-specific inferior statistical data and allows to develop a more flexible and versatile method for risk evaluation. Common risk factors and sub-factors for tourists were identified for further risk assessment using suggested by L. Zadeh Z-number. A bi-component Z-number Z = (A, B) with perception-based and imprecise parts A and B, allows taking into account the reliability of the information. Risk experts deal with the prediction like this one “very likely that the level of threat N is medium” or “extremely likely that this factor is very important”. This prediction can be formalized as a Z-number based evaluation and a pack of Z-valuations is considered as Z-information. Experts evaluate identified risk factors and sub-factors and their importance weight using Z-numbers.
Keywords: project approach, travel risk factors, tourism risk assessment, Z-number-based evaluation